Complete Pathologic Response to Pretransplant Locoregional Therapy for Hepatocellular Carcinoma Defines Cancer Cure After Liver Transplantation: Analysis of 501 Consecutively Treated Patients. Issue 3 (September 2015) - Agopian, Vatche G.; Morshedi, Maud M.; McWilliams, Justin; Harlander-Locke, Michael P.; Markovic, Daniela; Zarrinpar, Ali; Kaldas, Fady M.; Farmer, Douglas G.; Yersiz, Hasan; Hiatt, Jonathan R.; Busuttil, Ronald W.
Abstract : Objectives: To evaluate the rate, effect, and predictive factors of a complete pathologic response (cPR) in patients with hepatocellular carcinoma (HCC) undergoing locoregional therapy (LRT) before liver transplantation (LT). Background: Eligible patients with HCC receive equal model for end-stage liver disease prioritization, despite variable risks of tumor progression, waitlist dropout, and posttransplant recurrence. Pretransplant LRT mitigates these risks by inducing tumor necrosis. Methods: Comparisons were made among HCC recipients with cPR (n = 126) and without cPR (n = 375) receiving pre-LT LRT (1994–2013). Multivariable predictors of cPR were identified. Results: Of 501 patients, 272, 148, and 81 received 1, 2, and 3 or more LRT treatments. The overall, recurrence-free, and disease-specific survival at 1-, 3-, and 5 years was 86%, 71%, 63%; 84%, 67%, 60%; and 97%, 90%, 87%. Compared with recipients without cPR, cPR patients had significantly lower laboratory model for end-stage liver disease scores, pretransplant alpha fetoprotein, and cumulative tumor diameters; were more likely to have 1 lesion, tumors within Milan/University of California, San Francisco (UCSF) criteria, LRT that included ablation, and a favorable tumor response to LRT; and had superior 1-, 3-, and 5-year recurrence-free survival (92%, 79%, and 73% vs 81%, 63%, and 56%; P = 0.006) and disease-specific survival (100%, 100%, and 99% vs 96%, 89%, and 86%; P < 0.001) with only 1 cancer-specific death and fewer recurrences (2.4% vs 15.2%; P < 0.001). Multivariate predictors of cPR included a favorable post-LRT radiologic/alpha fetoprotein tumor response, longer time interval from LRT to LT, and lower model for end-stage liver disease score and maximum tumor diameter (C-statistic 0.75). Conclusions: Achieving cPR in patients with HCC receiving LRT strongly predicts tumor-free survival. Factors predicting cPR are identified, allowing for differential prioritization of HCC recipients based on their variable risks of post-LT recurrence. Improving LRT strategies to maximize cPR would enhance posttransplant cancer outcomes. Abstract : Posttransplant hepatocellular carcinoma (HCC) recurrence and survival were analyzed in 501 patients with HCC receiving pretransplant locoregional tumor therapy, including comparisons of recipients with (n = 126) and without (n = 375) a complete pathologic response (cPR). Recipients with cPR suffered only 1 cancer-specific mortality and demonstrated superior recurrence-free and cancer-specific survival.